Performance Assesment of Bauchi Polytechnics and Technical Colleges Using Quality Assurance Indicators in Nigeria Qualification Framework - Idris Adamu (UIN Sunan Gunung Djati Bandung, 2016)
Technical and Vocational Education emphases skill acquisition, Quality Assurance in vocational education is concept that is concerned with high performance involved activities with vocational education such as teaching, learning, infrastructures, student’s behavior and entire academic process. Good quality education is very necessary in the total development of staff and students which ensures proper development, job prospects and the realization of academic goals and objects. Enhanced and sustained to ensure accountability and improve performance. Higher educational institutions in Nigeria continue to experience carelessly attitude about the use of Quality Assurance to understand the risk they are exposed to poor standard. To address these issues, the study embarked upon to determine the level of performance and difference usability of Quality Assurance in Polytechnics and Technical Colleges in Bauchi state. Quantitative method technique was employed using survey questionnaires, 60 staff both senior and junior within these institutions were selected and a questionnaire distributed for their responses. The data were analysed using SPSS software. The result reveals that Federal Polytechnic Bauchi and State Polytechnic Bauchi has high level of Performance about Quality Assurance indicators while College of Education Azare has medium level of Performance. College of education Azare has highest mean rank of 29.87 and percentage of 31.8% obtained from the output result indicated that it has high usability to Quality Assurance, followed by Federal Polytechnic Bauchi with medium usability then State Polytechnic Bauchi has low usability to Quality Assurance. The study concluded by Quality Assurance Unit be made aware to each institution staff to enable recognize the benefits of it. Federal government should give more funding and employ staff to cater the need of Quality Assurance Unit in every institution so that it will help the students to develop their potentialities.